Nilai-Nilai Pendidikan Karakter Dalam Al-Qur’an Surat Al-‘Alaq Ayat 1-5 Perspektif Mufassir Nusantara - Niam, Khoirun (AL MURABBI, 2022)
This study aims to analyze the values of character education according to the Nusantara mufassir. Character education has become a model of education offered to overcome the moral problems of children in Indonesia. This is related to the increase in juvenile delinquency in society. Ulama' Mufassir Nusantara has contributed to building human resources in the archipelago through his book of interpretation. This research is a qualitative research in the form of literature study. The object of the research material is the book of interpretation by Ulama' Tafsir originating from the archipelago. The method is to determine the verses related to the values of character education, namely the Qur'an surah al-‘Alaq [96] verses 1-5. The results of the study show that the first verse was revealed to the Prophet Muhammad SAW., in line with the values of character education, namely the command to love reading, humans have the character of hard work, independence, and high curiosity. And the verse in question includes the character values needed by the Prophet Muhammad. as an initial provision in his missionary mission. These verses should also be instilled in all of his people.